Hubungan Status Gizi, Umur, Jenis Kelamin dengan Derajat Infeksi Dengue pada Anak di RSUD Abdul Wahab Sjahranie Samarinda: Relationship between Nutritional Status, Age, Gender and Degree of Dengue Infection in Children at Abdul Wahab Sjahranie Hospital Samarinda - Putri Lintang Kharisma; Annisa Muhyi; Eva Rachmi (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Dengue virus infection can manifest from mild to severe, which are undifferentiated fever, dengue hemorrhagic fever (DD), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS), respectively. Mild and severe dengue infection is difficult to distinguish early in the course of the disease, and the clinical course is also difficult to